Tartan Polonaise: Scottish Crime Fiction in Poland - Crickmar, Marta (Glottodidactica, 2014)
This paper examines the position of contemporary Scottish crime fiction in the Polish polysystem. It investigates the definition of tartan noir and the challenges the genre poses in translation.Such concerns seem especially valid in the case of Denise Mina in whose Paddy Meehan series, next to the female protagonist, one of the most important characters is the city of Glasgow with its menacing architecture and the coarse language of its inhabitants. Thus the second part of this paper analyses the Polish translations of Mina’s trilogy in order to show how the dialect and other culture-specific items have been dealt with by two Polish translators.